Pressure Overload Is Associated With Low Levels of Troponin I and Myosin Binding Protein C Phosphorylation in the Hearts of Patients With Aortic Stenosis - Copeland, O’neal; Messer, Andrew; Jabbour, Andrew; Poggesi, Corrado; Prasad, Sanjay; Marston, Steven (Frontiers in Physiology, 2020)
In previous studies of septal heart muscle from HCM patients with hypertrophic obstructive cardiomyopathy (HOCM, LVOT gradient 50-120mmHg) we found that the level of phosphorylation of troponin I (TnI) and myosin binding protein C (MyBP-C) was extremely low yet samples from hearts with HCM or DCM mutations that did not have pressure overload were similar to donor heart controls. We therefore investigated heart muscle samples taken from patients undergoing valve replacement for aortic stenosis, since they have pressure overload that is unrelated to inherited cardiomyopathy. 13 muscle samples from septum and from free wall were analysed(LVOT gradients 30-100 mmHg ) The levels of TnI and MyBP-C phosphorylation were determined in muscle myofibrils by separating phosphospecies using phosphate affinity SDS-PAGE and detecting with TnI and MyBP-C specific antibodies. TnI was predominantly monophosphorylated and total phosphorylation was 0.85±0.03 molsPi/mol TnI. This phosphorylation level was significantly different (p=< 0.0001) from both donor heart TnI (1.6±0.06 molsPi/mol TnI) and HOCM heart TnI (0.19±0.04 molsPi/mol TnI). MyBP-C is phosphorylated at up to 4 sites. In donor heart the 4P and 3P species predominate but in the pressure overload samples the 4P species was much reduced and 3P and 1P species predominated. Total phosphorylation was 2.0±0.2 molsPi/mol MyBP-C (n=8) compared with 3.4±0.07 (n=21) in donor heart and 1.1±0.1 (n=10) in HOCM heart. We conclude that pressure overload may be associated with substantial dephosphorylation of troponin I and MyBP-C.